Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/rda.13753
|View full text |Cite
|
Sign up to set email alerts
|

TGIF1 and SF1 polymorphisms are associated with litter size in Small Tail Han sheep

Abstract: TGF‐β induced factor homeobox 1 (TGIF1) and splicing factor 1 (SF1) are important for mammalian reproduction; however, the effects of these genes on litter size in sheep remain unexplored. In this study, we genotyped 768 ewes from seven sheep breeds at two loci: g.37871539C>T, a synonymous mutation of TGIF1; and g.42314637T>C, a 3′UTR variant of SF1. Our analysis of polymorphism revealed only two genotypes at locus g.37871539C>T in TGIF1, with most sheep populations being moderately polymorphic (0.25 < PIC < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Intronic mutations mostly affect mRNA shearing and folding at the molecular level and do not directly affect phenotypic traits (46, 47). For example, two intronic NOBOX mutations in Chinese women with premature ovarian failure (POF) were not associated with the disease (48), consistent with the intronic mutations in the present study, where g.1624 T>C, g.2770 G>A, and g.2821 A>G were not significantly associated with sow litter size traits (49,50). In the present study, the 3′-UTR mutation locus g.6025 T>A was significantly lower in the AA genotype, characterized by fewer litters and weaned piglets than in TT and TA genotypes in the second litter.…”
Section: Discussionsupporting
confidence: 80%
“…Intronic mutations mostly affect mRNA shearing and folding at the molecular level and do not directly affect phenotypic traits (46, 47). For example, two intronic NOBOX mutations in Chinese women with premature ovarian failure (POF) were not associated with the disease (48), consistent with the intronic mutations in the present study, where g.1624 T>C, g.2770 G>A, and g.2821 A>G were not significantly associated with sow litter size traits (49,50). In the present study, the 3′-UTR mutation locus g.6025 T>A was significantly lower in the AA genotype, characterized by fewer litters and weaned piglets than in TT and TA genotypes in the second litter.…”
Section: Discussionsupporting
confidence: 80%
“…It has also been shown that missense and intronic mutations cause changes in gene mRNA expression and that such changes are significantly associated with these two mutations [32]. The occurrence of synonymous mutations can have an effect on production traits, which has also been reported in several studies [33][34][35][36]. Studies have demonstrated that keratin, a target gene of Hoxc13, is critically regulated by Hoxc13 and also has a regulatory role in hair follicle development, and mutations in Hoxc13 have been shown to cause hair defects in mice and human patients [8,37,38].…”
Section: Identification Of Hoxc13 Polymorphisms and Association Analy...mentioning
confidence: 70%
“…Similar to previous studies, our study revealed that the TGIF1 missense variant g.37866222C > T showed a significant increase in LS at the second and third parity and that mutant-type ewes (CT) displayed the maximum LS (p < 0.05). However, the mutant homozygous genotype TT was not detected, similar to g.37871539C > T in TGIF1 (Zhang, 2020), indicating that lethality may be caused by mutant homozygous genotypes at some loci of TGIF1 in all sheep breeds. Moreover, cel- lular transmembrane domains enable numerous proteins to function on the fertility-related signaling pathway (Guna and Hegde, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Combined with our previous data on 768 sheep from seven breeds, which was collected via whole-genome resequencing, some SNPs were screened out (Zhang et al, 2019(Zhang et al, , 2020He et al, 2019), including rs421947730 and rs160510212 of FLT3; rs429977514, rs408772397, and rs426897754 of NLRP5; and g.37866222C > T and rs1092900782 of TGIF1. Primers to genotype these SNPs were designed by MassAR-RAY® Assay Design (v.3.1).…”
Section: Design Of the Primer And Synthesizing And Genotyping Of The Locusmentioning
confidence: 99%